PENGARUH UPAH TERHADAP MOTIVASI KERJA NARAPIDANA YANG MENGIKUTI PEMBINAAN PABRIK GARMEN DI LAPAS KELAS I MAKASSAR - Fachri Syawal; Mulyani Rahayu (Politeknik Negeri Ambon, 2022)
It should be noted that there are many factors that can motivate a person to perform at their best and salary is not the only one, but salary is a very significant motivating factor and can push a person to perform at their best. The inmate follows coaching by giving doing a profitable job. Therefore, they have the right to be paid for their hard work. The variables studied were the labor motivation wage variable of inmates involved in the construction of garment in Makassar Class I Correctional Institution, the method used in this study was quantitative research. In conducting the research, the author distributed questionnaires to 63 respondents in the form of inmates who had participated in clothing training sessions. The questionnaire used in this study consisted of 20 statement items on the research variables. When analyzing the data in this study using descriptive analysis through simple linear regression test, data normality test, significance test and determination test using IBM SPSS 25. When testing the research hypothesis, the researcher performed a t-test to find out which research hypotheses were accepted and rejected. Based on the results of the study, the value of t Count > t Table is (14,503 > 2,000). So this indicates that Ho is accepted, which means that there is an influence between the wage variable on the prisoner's work motivation variable. Then the percentage influence of the wage variable on the work motivation variable is given based on the results of the determination test of the R-squared value of 0.775. From this it follows that the influence of the wage variable on the work motivation variable is 77.5%. While the remaining 22.5% are influenced by other variables that are not explained in this study.